Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This is exercise from my lecturer, for IMC preparation. I haven't found any idea.

Find the value of

$$\lim_{n\rightarrow\infty}n^2\left(\int_0^1 \left(1+x^n\right)^\frac{1}{n} \, dx-1\right)$$

Thank you

share|cite|improve this question
up vote 8 down vote accepted

By integration by parts,

\begin{align*} \int_{0}^{1} (1 + x^{n})^{\frac{1}{n}} \, dx &= \left[ -(1-x)(1+x^{n})^{\frac{1}{n}} \right]_{0}^{1} + \int_{0}^{1} (1-x)(1 + x^{n})^{\frac{1}{n}-1}x^{n-1} \, dx \\ &= 1 + \int_{0}^{1} (1-x) (1 + x^{n})^{\frac{1}{n}-1} x^{n-1} \, dx \end{align*}

so that we have

\begin{align*} n^{2} \left( \int_{0}^{1} (1 + x^{n})^{\frac{1}{n}} \, dx - 1 \right) &= \int_{0}^{1} n^{2} (1-x) (1 + x^{n})^{\frac{1}{n}-1} x^{n-1} \, dx. \end{align*}

Let $a_{n}$ denote this quantity. By the substitution $y = x^{n}$, it follows that

\begin{align*} a_{n} &= \int_{0}^{1} n \left(1-y^{1/n}\right) (1 + y)^{\frac{1}{n}-1} \, dy = \int_{0}^{1} \int_{y}^{1} t^{\frac{1}{n}-1} (1 + y)^{\frac{1}{n}-1} \, dtdy \end{align*}

Since $0 \leq t (1 + y) \leq 2$ and $ \int_{0}^{1} \int_{y}^{1} t^{-1}(1+y)^{-1} \, dtdy < \infty$, an obvious application of the dominated convergence theorem shows that

\begin{align*} \lim_{n\to\infty} a_{n} = \int_{0}^{1} \int_{y}^{1} \frac{dtdy}{t(1+y)} &= - \int_{0}^{1} \frac{\log y}{1+y} \, dy \\ &= \sum_{m=1}^{\infty} (-1)^{m} \int_{0}^{1} y^{m-1} \log y \, dy = \sum_{m=1}^{\infty} \frac{(-1)^{m-1}}{m^2} = \frac{\pi^2}{12}. \end{align*}

share|cite|improve this answer
Nice work! Now it's proven :) – Start wearing purple Jul 3 '13 at 10:29
Very nice! The value of $\pi^2/12 = .822...$ falls within my bounds of .75 to .875 which is comforting. – marty cohen Jul 3 '13 at 13:33
@sos440 here is a shortcut I noticed. By DCT $ \lim_{n\to\infty}\int_{0}^{1} n \left(1-y^{1/n}\right) (1 + y)^{\frac{1}{n}-1} \, dy=\int_{0}^{1} \lim_{n\to\infty} \frac{\left(1-y^{1/n}\right)}{1/n} (1 + y)^{\frac{1}{n}-1} \, dy=-\int_{0}^{1}\frac{\log y}{1+y}\ dy=\frac{\pi^2}{12}$ – user 1618033 Jul 3 '13 at 19:30
@Chris'swisesister, that's my first approach but I was unsure if we can find a dominating function for $(1 - y^{1/n})/(1/n)$. This is why I introduced double integral. – Sangchul Lee Jul 4 '13 at 3:24

I get an answer that differs from that of user17762. This is because the error term is not one term of order $\frac{x^{2n}}{n^2}$ but a number of such terms.

I get that the limit is between 3/4 and 7/8, but only have an infinite series for the value.

My complete analysis follows.

$(1+x^n)^{1/n} =\sum_{k=0}^{\infty} \binom{1/n}{k}x^{kn} $.

We first look at $\binom{1/n}{k}$.

$\begin{align} \binom{1/n}{k} &=\frac1{k!}\prod_{i=0}^{k-1}(\frac{1}{n}-i)\\ &=\frac1{k!n^k}\prod_{i=0}^{k-1}(1-in)\\ &=\frac{(-1)^k}{k!n^k}(-1)\prod_{i=1}^{k-1}(in-1)\\ &=\frac{(-1)^{k+1}}{k!n^k}\prod_{i=1}^{k-1}(in-1)\\ \end{align} $


$\begin{align} \big|\binom{1/n}{k}\big| =\frac1{k!n^k}\prod_{i=1}^{k-1}(in-1) <\frac{1}{k!n^k}\prod_{i=1}^{k-1}(in) =\frac{n^{k-1}(k-1)!}{k!n^k} =\frac1{kn} \end{align} $


$\begin{align} \frac{\binom{1/n}{k+1}}{\binom{1/n}{k}} &=\frac{(-1)^{k+2}}{(k+1)!n^{k+1}}\frac{k!n^k}{(-1)^{k+1}}\frac{\prod_{i=1}^{k}(in-1)}{\prod_{i=1}^{k-1}(in-1)}\\ &=\frac{-1}{(k+1)n}(kn+1)\\ &=-\frac{kn+1}{kn+n}\\ \end{align} $

We now look at $\int_0^v (1+x^n)^{1/n}\, dx$ to see what happens as $v \to 1$.

$\begin{align} \int_0^v (1+x^n)^{1/n}\, dx &=\sum_{k=0}^{\infty} \binom{1/n}{k} \int_0^v x^{kn}\, dx\\ &=\sum_{k=0}^{\infty} \binom{1/n}{k} \frac{v^{kn+1}}{kn+1}\\ &=v+\frac{v^{n+1}}{n(n+1)}+\sum_{k=2}^{\infty} \binom{1/n}{k} \frac{v^{kn+1}}{kn+1}\\ &=v+\frac{v^{n+1}}{n(n+1)}+v^{2n+1}\sum_{k=2}^{\infty} \binom{1/n}{k} \frac{v^{(k-2)n}}{kn+1}\\ \end{align} $

This means that the terms in $\sum_{k=2}^{\infty} \binom{1/n}{k} \frac{v^{(k-2)n}}{kn+1} $ decrease in absolute value and, since they alternate in sign, the series converges. and converges even at $v=1$ because of the $\frac1{kn+1}$.

Let $f(v, n) = \sum_{k=2}^{\infty} \binom{1/n}{k} \frac{v^{(k-2)n}}{kn+1} $.

Since $\big|\binom{1/n}{k} \frac{1}{kn+1}\big| < \frac1{kn(kn+1)} $, $|f(v, n)| <\sum_{k=2}^{\infty} \frac1{kn(kn+1)} <\frac1{n^2}\sum_{k=2}^{\infty} \frac1{k^2} <\frac1{n^2} $.

The first term of $f(v, n)$ is $\binom{1/n}{2}\frac{1}{2n+1} =\frac{(1/n)(1/n-1)}{2}\frac{1}{2n+1} =-\frac{n-1}{2n^2(2n+1)} $ and this is between $-\frac1{8n^2}$ and $-\frac1{4n^2}$ for $n > 3$.

Therefore the first two terms of the expansion of $\int_0^v (1+x^n)^{1/n}\, dx$ are both of order $1/n^2$, so we have to consider the whole sum, not just the first term (after $1$).

Since $\int_0^v (1+x^n)^{1/n}\, dx =v+\frac{v^{n+1}}{n(n+1)}+v^{2n+1}f(v, n) $ and all the terms exist as $v \to 1$, $\int_0^1 (1+x^n)^{1/n}\, dx -1-\frac{1}{n(n+1)}=f(1, n) $.

Since $f(1,n)$ is between $-\frac1{8n^2}$ and $-\frac1{4n^2}$, $-\frac1{4n^2} <\int_0^1 (1+x^n)^{1/n}\, dx -1-\frac{1}{n(n+1)} <-\frac1{8n^2} $, $-\frac1{4} <n^2\big(\int_0^1 (1+x^n)^{1/n}\, dx -1\big)-\frac{n}{n+1} <-\frac1{8} $ so $1-\frac1{4} <\lim_{n \to \infty} n^2 \big(\int_0^1 (1+x^n)^{1/n}\, dx -1\big) < 1-\frac1{8} $.

share|cite|improve this answer
+1. Actually, I have found that the exact value is equal to $\pi^2/12$. – Start wearing purple Jul 3 '13 at 7:58

Mathematica evaluates the integral to $$\int_0^{1}(1+x^n)^{1/n}dx={}_2F_1\left(-\frac{1}{n},\frac1n,1+\frac1n;-1\right).\tag{1}$$ Next, let us write the standard series representation for the hypergeometric function $$_2F_1(a,b,c;t)=\sum_{k=0}^{\infty}\alpha_kt^k,\qquad \alpha_k=\frac{\Gamma(a+k)\Gamma(b+k)\Gamma(c)}{k!\,\Gamma(a)\Gamma(b)\Gamma(c+k)}.$$ Now an easily verified claim: as $n\rightarrow\infty$, for the parameters as in (1), we have $\alpha_0=1$ and $$\alpha_k\sim-\frac{1}{k^2n^2}+O(n^{-3}).$$ Hence we obtain \begin{align} \lim_{n\rightarrow\infty}n^2\left(\int_0^{1}(1+x^n)^{1/n}dx-1\right)=\sum_{k=1}^{\infty}\frac{(-1)^{k+1}}{k^2}=\frac{\pi^2}{12}, \end{align} which is also confirmed by numerical calculation with $n\sim 10^4-10^8$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.